2010
DOI: 10.2478/v10042-008-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha and its receptors in epithelial ovarian cancer.

Abstract: Abstract:The aim of the present study was to characterize the expression pattern of tumor necrosis factor (TNF)-α and its receptors (TNF-Rs) in the epithelial ovarian cancer (EOC) and compare these results with the outcome of 126 patients. Presence of TNF-α, TNFR-1 and TNFR-2 were studied by Western blotting and immunohistochemistry. The proportion of samples positive for TNF-α and TNF-R2 was higher in epithelial ovarian cancer patients than in benign ovarian diseases (p<0.001 and p=0.016, respectively). Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…In human cancers, the expression of TNFRs implicates different aspects of TNFR functions. In epithelial ovarian cancer, the expression of TNFR2 was higher in epithelial ovarian cancer patients than in benign ovarian diseases; the expression intensity of TNFR2 was correlated with tumor stage and with reduced mean survival time [20]. In diffuse large B cell lymphoma, Nakayama found that TNFR1-positive expression was associated with a poorer overall survival.…”
Section: Discussionmentioning
confidence: 96%
“…In human cancers, the expression of TNFRs implicates different aspects of TNFR functions. In epithelial ovarian cancer, the expression of TNFR2 was higher in epithelial ovarian cancer patients than in benign ovarian diseases; the expression intensity of TNFR2 was correlated with tumor stage and with reduced mean survival time [20]. In diffuse large B cell lymphoma, Nakayama found that TNFR1-positive expression was associated with a poorer overall survival.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, increased TNF-α concentrations were observed in cancer tissues and ascites [ 225 ]. Cancer patients were also characterized by overexpression of receptor TNF-R2, which was further correlated with tumor stage and patient prognosis [ 226 ]. TNF-α is produced by tumor cells, and studies devoted to EOC indicated its multidirectional activity, as an autocrine stimulator of tumor progression and neovascularization as well as a downregulator of Tregs and enhancer of the host immunity against tumor [ 54 , 227 -229 ].…”
Section: Tumor Necrosis Factor-αmentioning
confidence: 99%
“…Increased TNF-α concentrations have been observed in ovarian cancer patients in serum and cyst fluid, as well as in cancer tissues and ascites [310,311]. Cancer patients have also been characterized by overexpression of receptor TNF-R2, which was further correlated with tumor stage and patient prognosis [312]. TNF-α expressed on tumor cells orchestrates the paracrine "TNF network", and together with IL-6 and CXCL12 regulates tumor growth [313].…”
Section: Inflammation and Cancer Escapementioning
confidence: 99%